2019
DOI: 10.1074/jbc.ra119.008947
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule analysis reveals rotational substeps and chemo-mechanical coupling scheme of Enterococcus hirae V1-ATPase

Abstract: V1-ATPase (V1), the catalytic domain of an ion-pumping V-ATPase, is a molecular motor that converts ATP hydrolysis–derived chemical energy into rotation. Here, using a gold nanoparticle probe, we directly observed rotation of V1 from the pathogen Enterococcus hirae (EhV1). We found that 120° steps in each ATP hydrolysis event are divided into 40 and 80° substeps. In the main pause before the 40° substep and at low ATP concentration ([ATP]), the time constant was inversely proportional to [ATP], indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(85 citation statements)
references
References 80 publications
6
78
1
Order By: Relevance
“…In this study, by using scattering imaging of gold nanoparticle (AuNP), we visualized load-free fast stepping motion of artificially-dimerized chimeric dynein with 100 µs time resolution and sub-nanometer localization precision at physiologically-relevant 1 mM ATP. Since AuNP strongly scatters light at its plasmon resonance wavelength without suffering from photobleaching and blinking, it has been used as a probe of single-molecule imaging of linear and rotary motor proteins in vitro [17][18][19][20][21][22][23][24][25] and imaging of intracellular cargo transport [26][27][28] . We analyzed trajectory of the stepping motion of the chimeric dynein in detail, including the step size, preference of the step direction, and dwell time, and revealed that this chimeric dynein moves with biased small stepping motion in which only backward steps are slightly suppressed compared to forward and side steps.…”
mentioning
confidence: 99%
“…In this study, by using scattering imaging of gold nanoparticle (AuNP), we visualized load-free fast stepping motion of artificially-dimerized chimeric dynein with 100 µs time resolution and sub-nanometer localization precision at physiologically-relevant 1 mM ATP. Since AuNP strongly scatters light at its plasmon resonance wavelength without suffering from photobleaching and blinking, it has been used as a probe of single-molecule imaging of linear and rotary motor proteins in vitro [17][18][19][20][21][22][23][24][25] and imaging of intracellular cargo transport [26][27][28] . We analyzed trajectory of the stepping motion of the chimeric dynein in detail, including the step size, preference of the step direction, and dwell time, and revealed that this chimeric dynein moves with biased small stepping motion in which only backward steps are slightly suppressed compared to forward and side steps.…”
mentioning
confidence: 99%
“…In the 120° step rotation, the designed V1 was found to have the main-pauses and sub-pauses before the 40° and 80° sub-steps respectively, which is the same as the wild-type V1 28 (Fig. 5a).…”
Section: Adp-release At the Catalytic Site Is Facilitated Allostericallymentioning
confidence: 63%
“…The designed B-subunit (De), expressed with the A-subunit in E. coli using the plasmid pTR19-AB 28 and purified by a Ni 2+ -affinity chromatography followed by size exclusion chromatography, formed a ring complex with the A-subunit (A3(De)3 ring complex) ( Supplementary Fig. 7a).…”
Section: Designed B-subunits Forms a Ring Complex With A-subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are only two wellcharacterized V-ATPases for which the number of rotational steps in V 1 and number of proton-carrying units in V o is known. One of them is the Enterococcus hirae V-ATPase (EhV), with a 6-step V 1 (Iida et al 2019) and a V o with 10 proton-carrying units (Murata et al 2005), providing support for the abovementioned correlation. The other one is the V-ATPase from Thermus thermophilus (ThV), which consists of a 3-step V 1 (Furuike et al 2011) and a V o with 12 proton-carrying units (Toei et al 2007).…”
Section: Stoichiometry Of H + Per Turn Of F Omentioning
confidence: 90%